Raising Healthy Children: Introducing New Foods to Your Preschooler - Julie M. Martinez; Karla P. Shelnutt (EDIS)
FCS8891, a 3-page illustrated fact sheet by Julie M. Martinez and Karla P. Shelnutt, discusses different ways to encourage children to try and accept new foods. Includes references. Published by the UF Department of Family Youth and Community Sciences, January 2010.